FACTORS AFFECTING NUTRITIONAL STATUS IN CHILDREN IN COT PEURADI VILLAGE, SUKA MAKMUE DISTRICT NAGAN RAYA DISTRICT - Fitri Yani; Marniati; Safrizal; Fikri Faidul Jihad; Enda Silvia Putri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The nutritional status of Suka Makmue District in 2019 has a nutritional status rate of 27.8%, the number of cases of wasting reaches 9.1%, and cases of underweight with a rate of 13.1% (50%). (Puskemas Cot Kuta, Suka Makmue District, Nagan Raya Regency 2019). In 2020 in Suka Makmue District, cases of nutrition were at 30%, cases of wasting were 8.90%, and underweight were at 12.85%. 2021 nutritional status reaches 20% while toddlers who experience malnutrition are 8.88%. 2022 states that data on the nutritional status of toddlers has decreased by 2.8% to 21.6%. carried out in this problem of nutritional status. determine the factors that cause nutritional status problems that cause nutritional status events in the working area of ​​Posyandu Cot Peuradi, Nagan Raya Regency. Method: this study uses a quantitative method with a Cross Sectional Study approach. The population in this study were all toddlers in the Posyandu Cot Peuradi data and the sample used was 30 toddlers, using the sampling method of sampling. The results showed that there was a significant influence between knowledge and cases of malnutrition (p-value = 0.07), patterns of feeding children (p-value = 0.000), or family income (p-value = 0.013). Because it is not a problem in the health sector that can easily be cured and requires willingness from the start at the prevention stage, this case starts with the prospective mother and father. Because childhood, which is composed in the first 1000 days of life, greatly influences what events can happen to children.